Effects of recovery type after a judo match on blood lactate and performance in specific and non-specific judo tasks - Franchini, E.; de Moraes Bertuzzi, R. C.; Takito, M. Y.; Kiss, M. A. P. D. M. (European Journal of Applied Physiology, 2009)
The objective of the present study was to verify if active recovery (AR) applied after a judo match resulted in a better performance when compared to passive recovery (PR) in three tasks varying in specificity to the judo and in measurement of work performed: four upper-body Wingate tests (WT); special judo fitness test (SJFT); another match. For this purpose, three studies were conducted. Sixteen highly trained judo athletes took part in study 1, 9 in study 2, and 12 in study 3. During AR judokas ran (15 min) at the velocity corresponding to 70% of 4 mmol/l blood lactate intensity (~50% VO2VO2peak), while during PR they stayed seated at the competition area. The results indicated that the minimal recovery time reported in judo competitions (15 min) is long enough for sufficient recovery of WT performance and in a specific high-intensity test (SJFT). However, the odds ratio of winning a match increased ten times when a judoka performed AR and his opponent performed PR, but the cause of this phenomenon cannot be explained by changes in number of actions performed or by changes in match`s time structure.